Brill's companion to German platonism - Kim, Alan, 1968- (Brill's Companions to Philosophy, 2015)
For six centuries, Plato has held German philosophy in his grip. Brill's Companion to German Platonism examines how German thinkers have interpreted Plato and how in turn he has decisively influenced their thought. Under the editorship of Alan Kim, this companion gathers the work of scholars from four continents, writing on figures from Cusanus and Leibniz to Husserl and Heidegger. Taken together, their contributions reveal a characteristic pattern of "transcendental" interpretations of the mind's relation to the Platonic Forms. In addition, the volume examines the importance that the dialogue form itself has assumed since the nineteenth century, with essays on Schleiermacher, the Tübingen School, and Gadamer. Brill's Companion to German Platonism presents both Plato and his German interpreters in a fascinating new light.